Analisis Kesalahan Tulis Pada Teks Narasi Karya Siswa Kelas V SDN 34 Mataram - Wardani, Iqlima; Witono, A. Hari; Setiawan, Heri; Aji, Styo M. W. (Primera Educatia Mandalika: Elementary Education Journal, 2024)
This research aims to describe writing errors in the narrative texts of class V students at SDN 34 Mataram in the 2019/2020 academic year. This research is qualitative research with descriptive methods. The object of this research is 27 narrative texts written by class V students at SDN 34 Mataram. The sampling technique used was purposive sampling. The technique used in collecting data is triangulation including interview techniques, documentation and test techniques. This triangulation technique is also a test of data credibility, where when the data collected through these three techniques produces the same data, the research is said to be credible. The researcher is the key instrument in this research, then the researcher also uses interview guides and tests as supporting instruments. The research results showed that errors in the use of word choice (diction) were the most common errors, amounting to 187 errors with a percentage of 42.43%. Errors in using dots resulted in 116 errors with a percentage of 26.30%. The next mistake that students often make is the error in using capital letters. There were 78 errors made by students in using capital letters with a percentage of 17.69%. The errors made by students were errors in using the words in, to and from as well as errors in using commas which amounted to 23 and 37 respectively with percentages of 5.22% and 8.39%. The suggestion given is for teachers to carry out more intensive learning, especially paying more attention to the writing aspect. Apart from that, students are also expected to practice a lot through teacher guidance.